2009
DOI: 10.1165/rcmb.2008-0276oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Multiwalled Carbon Nanotubes Potentiate Airway Fibrosis in Murine Allergic Asthma

Abstract: Carbon nanotubes are gaining increasing attention due to possible health risks from occupational or environmental exposures. This study tested the hypothesis that inhaled multiwalled carbon nanotubes (MWCNT) would increase airway fibrosis in mice with allergic asthma. Normal and ovalbumin-sensitized mice were exposed to a MWCNT aerosol (100 mg/m(3)) or saline aerosol for 6 hours. Lung injury, inflammation, and fibrosis were examined by histopathology, clinical chemistry, ELISA, or RT-PCR for cytokines/chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
212
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(238 citation statements)
references
References 35 publications
21
212
2
1
Order By: Relevance
“…For example, our earlier studies found that MWCNTs with a length of 10-100 μm impaired pulmonary function 22 and induced severe cardiac ischemic/ reperfusion injury after pulmonary instillation. 23 Similar results on MWCNT toxicity were also reported elsewhere, [24][25][26][27] such as subchronic toxicity, asbestos-like pathogenicity in mice, and airway fibrosis. In contrast, CNTs with a length shorter than 2 μm have been shown to exhibit minimal toxicity to various cell types, such as human promyelocytic leukemia (HL60) and human T-cells (Jurkat).…”
supporting
confidence: 81%
“…For example, our earlier studies found that MWCNTs with a length of 10-100 μm impaired pulmonary function 22 and induced severe cardiac ischemic/ reperfusion injury after pulmonary instillation. 23 Similar results on MWCNT toxicity were also reported elsewhere, [24][25][26][27] such as subchronic toxicity, asbestos-like pathogenicity in mice, and airway fibrosis. In contrast, CNTs with a length shorter than 2 μm have been shown to exhibit minimal toxicity to various cell types, such as human promyelocytic leukemia (HL60) and human T-cells (Jurkat).…”
supporting
confidence: 81%
“…There are few studies that have developed aerosolization systems and delivered carbon-based nanomaterials via inhalation (Li et al 2007;Mitchell et al 2007;Ryman-Rasmussen et al 2008;Shvedova et al 2008). In the Mitchell et al (2007) study, MW-CNTs were aerosolized with a jet mill coupled to a dry chemical screw feeder and a 2-µm cut-point cyclone.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a system encompassing an acoustic fluidization feeder, mill, and size separator was used to generate aerosolized single-walled carbon nanotubes (SW-CNTs; Baron et al 2008), whereas a jet mill coupled to a dry chemical screw feeder (Mitchell et al 2007) or a 6-jet collision nebulizer (Ryman-Rasmussen et al 2008) was utilized to aerosolize multiwalled carbon nanotubes (MW-CNTs). Other test systems employed for generating nanomaterials have included a brush dust generator for inhalation studies of nanotitanium dioxide (Ma-Hock et al 2009), as well as a direct delivery of aerosolized nanomaterials from an evaporation reactor (e.g., silicon dioxide; Ostraat et al 2008) or combustion with a laminar diffusion flame system (e.g., ultrafine iron; Yang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Such events result in protracted AM release of inflammatory cytokines, chemokines, interferons, and other soluble mediators; further recruitment of immune effector cells; increased production/release of free radicals (eg, reactive oxygen species [ROS]); and possible damage to the delicate underlying alveolar epithelium. These events may be a precursor to known MWCNT-induced pathologies such as pulmonary fibrosis 19 and granulomatous inflammation 20 in rodents following inhalation. Previous work in our laboratory showed that the length of MWCNTs is a critical determinant of their adverse bioreactivity with primary human AMs (in terms of proinflammatory mediator release and cell death); following an acute (24 hours) treatment, AMs displayed greatest reactivity toward long MWCNTs (~20 μm in length) than toward short MWCNTs (~0.6 μm in length).…”
Section: Introductionmentioning
confidence: 99%